USE OF METHODS IN TEACHING FOREIGN LANGUAGES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Innovative methods that contribute to the development of creative functions of future teachers are manifested in several f absolute level; conditional level; subjective level. The orms, depending on the degreeof novelty: absolute level; local tion of innovative pedagogical innovations in practice is interpreted as a . . ,opinions mass applica criterion for their evaluation. This is mainly related to the technical support of the educational process and the specificity of the teacher's activity. The article gives and recommendations on this